246 The international gynecologic cancer society global curriculum: partnerships building capacity and expertise in gynecologic oncology for the world's poorest women. (18th September 2019) - Randall, T; Ng, J; Schmeler, K; Dinh, T; Nout, R; Eiken, M; Covens, A; Chuang, L; Quinn, M
Abstract : Objectives: Women in low- and middle-income countries (LMICs) have higher rates of cervical cancer and comparable rates of other gynecologic cancers when compared to women in high-income countries, yet the majority of LMICs have few gynecologic oncologist and lack formal training programs. The management of gynecologic cancers must be adapted to available resources and to potential differences in disease presentation and biology in LMICs. Methods: We developed an adaptable but universal curriculum for training in low resource settings. We supported collaborations between high- or middle-income country academic gynecologic oncologists and local mentors and trainees to either launch or strengthen formal gynecologic oncology fellowships. Milestones include: progression through the curriculum, clinical training with local and international mentors, regular Project ECHO tumor boards, logging of cases and educational activities, and observerships at the international mentor's institution. Trainees sit for a final examination; those who pass are awarded a certificate of completion from IGCS. Results: In 2019, IGCS is supporting 12 collaborative fellowships. Thirty fellows are in training, supported by 35 international mentors and 24 local mentors, and they have logged 1019 surgical procedures to date. Four major textbooks and the ACOG Prolog series have been donated to fellows. Forty-seven Project ECHO tumor boards were held in 2018. Fellows have traveled to host institutions in North America, Europe and Asia, and have attended international professional society meetings. Conclusions: The IGCS Global Curriculum is a novel model of sustained collaboration yielding academic quality, sub-specialty surgical training in resource limited settings that may be adapted to other specialties.